2022
DOI: 10.1097/md.0000000000030365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for bile duct injury in laparoscopic cholecystectomy in China: A systematic review and meta-analysis

Abstract: Background: To explore the risk factors of bile duct injury in laparoscopic cholecystectomy (LC) in China through meta-analysis. Methods: The study commenced with a search and selection of case–control studies on the risk factors for bile duct injury in LC in China using the following databases: PubMed, EMBASE, ScienceNet.cn, CNKI, Wanfang Data, and VIP. Data were extracted from the collected documents independently by 2 researchers, following which a meta-analysis of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The reported incidence of iatrogenic BDI in patients undergoing laparoscopic cholecystectomy ranges between 0.07 and 1.1 % in the literature [ 11 , 12 ]. While there is no evidence to suggest that SIT increases the risk of BDI following laparoscopic cholecystectomy [ 13 ], the anatomical variation associated with SIT is a potential risk factor that may contribute to a higher incidence of BDI after the procedure [ 14 , 15 ]. Furthermore, several other factors may contribute to an increased risk of BDI in patients with SIT: A delay in the diagnosis and management of gallbladder disease can occur if the patient's SIT status is unknown beforehand [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of iatrogenic BDI in patients undergoing laparoscopic cholecystectomy ranges between 0.07 and 1.1 % in the literature [ 11 , 12 ]. While there is no evidence to suggest that SIT increases the risk of BDI following laparoscopic cholecystectomy [ 13 ], the anatomical variation associated with SIT is a potential risk factor that may contribute to a higher incidence of BDI after the procedure [ 14 , 15 ]. Furthermore, several other factors may contribute to an increased risk of BDI in patients with SIT: A delay in the diagnosis and management of gallbladder disease can occur if the patient's SIT status is unknown beforehand [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review and meta-analysis in China, the incidence rate of BDI was 1.12% (16). In a large study in India (17), it was 0.05%, and in a local study (Sulaimani, Kurdistan region, Iraq) (18), it was 0.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Reinsoo et al ( 15 ) over 11 years, 241 BDIs were reported among 29,739 LCs (0.81%): 0.68% were minor injuries and 0.13% were major injuries. According to a systematic review and meta-analysis in China, the incidence rate of BDI was 1.12% ( 16 ). In a large study in India ( 17 ), it was 0.05%, and in a local study (Sulaimani, Kurdistan region, Iraq) ( 18 ), it was 0.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the intricate nature and heightened potential for postoperative complications, it is common practice to circumvent such issues whenever feasible (16) . Yang et al (17) reported that the revealed risk factors for bile duct injury were abnormal preoperative liver function, acute and subacute inflammation of gallbladder, thickening of gallbladder wall (≥4 mm), cholecystolithiasis complicated with effusion, and the anatomic variations of the gallbladder triangle. However, the factors of gender and overweight (body mass index ≥ 25 kg/m 2 ) were not significantly correlated with bile duct injury in LC.…”
Section: Discussionmentioning
confidence: 99%